The Position Of Commitment-Making Officials As Legal Subjects In Disputes Over Construction Service Agreements In Indonesian Courts - Siti Marfungah; Suartini Suartini (Green Publisher Indonesia, 2024)
The role of the Commitment Making Officer (CMO) is crucial because they are responsible for the procurement process and contract implementation. However, disputes often occur regarding the CMO's legal position in the agreement. This study aims to examine in depth how courts in Indonesia view and regulate the legal position of CMO as a legal subject in the settlement of construction service agreement disputes. This study uses normative legal research methods with legislative and comparative approaches. The results showed that courts in Indonesia tend to position CMO as a legal subject that has significant responsibilities in construction service agreement disputes. CMOs are given the role of being responsible for the implementation of the contract and can be a party directly involved in dispute resolution in court. The analysis also reveals variations in the legal treatment of CMOs from case to case, highlighting the complexities in the interpretation and application of the relevant laws. Recommendations from this research include the need for further clarification in the legal regulations governing the position of CMOs, as well as the importance of better legal education regarding the responsibilities of CMOs in the context of construction service agreement disputes.